Integra's legacy unveiled: expert panel recommendations summarizing 25 years of experience in head and neck reconstruction - Prof. Franco Bassetto; Prof. Juan Carlos Lopez-Gutierrez; Prof. Riccardo Giunta; Benedetta Scucchi; Prof. Mark Singh; Prof. Cesare Tiengo (JPRAS Open)
Summary: Background: Integra® Dermal Regeneration Template (IDRT) is used for its ability to facilitate wound closure and mimic various skin functions, marking a breakthrough in medical technology. Methods: Through a synthesis of expert opinions, clinical experiences, and published evidence, this review sheds light on current applications of IDRT in head and neck wound care. Results: This review covers the application of IDRT for post-oncological surgery reconstructions, trauma-induced injuries, and scar corrections. It focuses on the use of IDRT in specific anatomical regions (scalp, temporal, orbital, nasal areas, neck, and ears) and in pediatric and older patients. The economic aspects, including cost-effectiveness and value in the healthcare system, are also examined. Conclusions: The insights presented aim to inform clinicians and encourage the broader integration of IDRT into clinical practice, enhancing patient outcomes in wound management.